Performing performance: young aspiring athletes’ presentation of athletic identity - Skilbred, Anette; Strandbu, Åse; Loland, Sigmund (Frontiers in Sports and Active Living, 2024)
Youths are in the process of figuring out answers to the question “who am I?” and young athletes are searching for athletic identity in interaction with their friends, teammates, coaches, and so on. This study explores athletes' presentations of athletic identity based on 24 interviews with ambitious young athletes attending upper secondary sport schools. Anchored in Goffman's theory of the self and the presentation of the self, as well as Markus and Nurius' concept of possible selves, the study views identity as socially constructed in interaction. Utilising this theoretical perspective alongside thematic analysis resulted in four themes that reveal characteristics that are deemed central in an athletic identity. First, the theme I am a dutiful athlete constitutes integral facets of the athletes' self-presentation as committed and diligent individuals. The interviews also bring to light variations in the athletes' attitudes and approaches towards these expectations and concepts. The remaining three themes: I must be unique, We must be unique, and I must have fun, illustrate how being a performing athlete extends beyond duties tied to training, resting, and eating. While the findings suggest the existence of certain dominant and desirable characteristics in an athletic identity, they also highlight variations in identities, emphasising negotiation and flexibility in handling the athlete role.